ECOLOGICALLY SUSTAINABLE DEVELOPMENT IN INNOVATION-ORIENTED REGIONAL ECONOMY - Anatoly I. Belousov; Elena A. Shelukhina (Вестник Северо-Кавказского федерального университета)
The article provides dwells on the methodological basics of ecologically stable development of innovation-oriented economy, which are the theoretical basis for constructing economic-mathematical models of ecology-economic systems and their use for solving relevant ecology-economic tasks of applied nature.